Cognitive performance profiles by latent classes of drug use - Bolla, K. I. (The American journal on addictions, 2014)
Background and Objectives: The relationship between substance use and cognitive deficits is complex and requires innovative methods to enhance understanding. The present study is the first to use LCA to examine associations of drug use patterns with cognitive performance. Methods: Cocaine/heroin users (N = 552) completed questionnaires, and cognitive measures. LCA identified classes based on past-month drug use and adjusted for probabilities of group membership when examining cognitive performance. Latent indicators were: alcohol (ALC), cigarettes (CIG), marijuana (MJ), crack smoking (CS), nasal heroin (NH), injection cocaine (IC), injection heroin (IH), and injection speedball (IS). Age and education were included as covariates in model creation. Results: Bootstrap likelihood ratio test (BLRT) supported a 5-class model. Prevalent indicators (estimated probability of over 50%) for each class are as follows: “Older Nasal Heroin/Crack Smokers” (ONH/CS, n = 166.9): ALC, CIG, NH, CS; “Older, Less Educated Polysubstance” (OLEP, n = 54.8): ALC, CIG, CS, IH, IC, and IS; “Younger Multi-Injectors” (MI, n = 128.7): ALC, CIG, MJ, IH, IC, and IS; “Less Educated Heroin Injectors” (LEHI, n = 87.4): CIG, IH; and “More Educated Nasal Heroin” users (MENH, n = ALC, CIG, NH. In general, all classes performed worse than established norms and older, less educated classes performed worse, with the exception that MENH demonstrated worse cognitive flexibility than YMI. Discussion and Conclusions: This study demonstrated novel applications of a methodology for examining complicated relationships between polysubstance use and cognitive performance. Scientific Significance: Education and/or nasal heroin use are associated with reduced cognitive flexibility in this sample of inner city drug users